Molecular Mechanisms of AMH Signaling - Howard, James A.; Hart, Kaitlin N.; Thompson, Thomas B. (Frontiers in Endocrinology, 2022)
Anti-Müllerian Hormone (AMH) is a secreted glycoprotein hormone with critical roles in reproductive development and regulation. Its chemical and mechanistic similarities to members of the Transforming Growth Factor β (TGF-β) family have led to its placement within this signaling family. As a member of the TGF-β family, AMH exists as a noncovalent complex of a large N-terminal prodomain and smaller C-terminal mature signaling domain. To produce a signal, the mature domain will bind to the extracellular domains of two type I and type II receptors which results in an intracellular SMAD signal. Interestingly, as will be discussed in this review, AMH possesses several unique characteristics which set it apart from other ligands within the TGF-β family. In particular, AMH has a dedicated type II receptor, Anti-Müllerian Hormone Receptor Type II (AMHR2), making this interaction intriguing mechanistically as well as therapeutically. Further, the prodomain of AMH has remained largely uncharacterized, despite being the largest prodomain within the family. Recent advancements in the field have provided valuable insight into the molecular mechanisms of AMH signaling, however there are still many areas of AMH signaling not understood. Herein, we will discuss what is known about the biochemistry of AMH and AMHR2, focusing on recent advances in understanding the unique characteristics of AMH signaling and the molecular mechanisms or receptor engagement.